Hypoxanthine guanine phosphoribosyl transferase deficiency presenting with gout and renal failure in infancy. Issue 10 (October 1983) - Holland, P C; Dillon, M J; Pincott, J; Simmonds, H A; Barratt, T M
Abstract : A month old infant had gout and renal failure caused by hypoxanthine guanine phosphoribosyl transferase (HGPRTase) deficiency. Investigations showed a high uric acid value, crystal nephropathy on ultrasound, and uric acid deposition on renal biopsy. The HGPRTase value was low in red cells and fibroblasts.